Understanding Leadership in Formal Organizations: Insights from Qualitative Research - Astawa, I Nengah Dasi; Putra, Made Satria Pramanda; Yustiani, Dwi; Putra, Komang Satria Wibawa (Institut Pariwisata dan Bisnis Internasional, 2024)
This qualitative empirical study investigates leadership styles in formal organizations. The study utilized purposive sampling to select informants, and data was collected through observation and interviews. The snowball model was employed when data saturation was achieved. The qualitative descriptive analysis of the data involved data collection, classification, reduction, and interpretation. The study findings indicate that leaders in formal organizations predominantly utilize collaborative, participative, and democratic leadership styles, with occasional employment of autocratic style in specific situations. Transformational leadership style is less commonly observed, particularly in the public sector, while there is an emerging trend towards its adoption in the private sector. The study highlights that the participative leadership style involves decision-making through selection, the democratic style is based on election, and the transformative leadership style is rooted in education.